MEASURING THE WANDERING MIND: USING PUPILLOMETRY TO ASSESS AGE DIFFERENCES IN OFF-TASK THOUGHTS DURING READING. (11th November 2018) - Shake, M; Mathews, R; Hughes, M; Meehan, C; Anderson, A; Zwakenberg, A
Abstract: Mind-wandering (MW) during reading is a pervasive phenomenon associated with a variety of negative consequences, such as poor comprehension. Interestingly, older adults self-report less MW than younger adults; however, such self-report measures are vulnerable to age differences in reporting bias. Recently, it was shown in younger adults that MW is reflected in increased pupil dilation and blinking rates. The present study investigated whether such pupillometric markers could be used to distinguish age differences in MW. Older and younger participants read a text while wearing an EyeLink II eye-tracker. At random intervals (every 2–4 minutes), the computer interrupted their reading to probe participants whether they had been MW. Pupillometric data were extracted from the 40 words prior to each random probe. Among those who experienced probe-caught episodes of both MW and on-task reading (22 Younger, 19 Older), pupillometric variables (e.g., age-normalized dilation, blinks, fixations) were each assessed in a 2 (Age) x 2 (Probe: Off-Task vs. On-Task) ANOVA. Results showed an effect of MW on Pupil Dilation, F(1, 39)=4.09, p=.05, such that participants' pupils were more dilated during episodes of MW. There was also a main effect of Age, F(1, 39)=7.72, p<.01, indicating greater age-normalized pupil size in older adults. The interaction was not significant, F(1, 39)=1.16, ns. These results indicate pupillometry can be a useful objective tool in understanding MW in older adults. Results are discussed and compared to research in other areas that has reported age differences in pupillary factors as a function of cognitive load.